1968
DOI: 10.1007/bf02890715
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of aflatoxin levels in cottonseed and peanut meals by ozonization

Abstract: Cottonseed and peanut meals were treated with ozone to destroy or eliminate aflatoxins. High meal moistures (cottonseed 22%, peanut 30%), high temperature (100C), and longer treatment times favored inactivation as measured by thinlayer chromatography. Aflatoxins B1 and G1 were readily destroyed by the ozone processes whereas aflatoxin Be appeared relatively resistant. In cottonseed meal, 91% of the total aflatoxins was destroyed in 2 hr, a decrease from 214 to 20 ppb ; in peanut meal, 78% was destroyed in 1 hr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

1972
1972
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 10 publications
0
23
0
2
Order By: Relevance
“…Several strategies for the detoxification of aflatoxins by physical, chemical and biological means have been reported (Ciegler, Lillehoj, Peterson, & Hall, 1966;Cole & Kirksey, 1971;Harvey, Kubena, Phillips, Huff, & Corrier, 1989;Mann & Rehm, 1976). These include chemical detoxification by ammoniation (Coker, Jewers, & Jones, 1985;Frayssinet & Lafarge, 1990;Gardner, Koltun, Dollear, & Rayner, 1971), treatment with formaldehyde and calcium hydroxide (Codifer, Mann, & Dollear, 1976), ozonization (Dwarakanath, Rayner, Mann, & Dollear, 1968), exposure to chlorine gas (Fischbach & Campbell, 1965) and hydrogen peroxide (Sreenivasamurthy, Parpia, Srikanta, & Shankar Murti, 1967). Other effective methods include microbial detoxification by Flavobacterium aurantiacum (Ciegler et al, 1966;Hao & Brackett, 1988), Mucor sp.…”
Section: Introductionmentioning
confidence: 95%
“…Several strategies for the detoxification of aflatoxins by physical, chemical and biological means have been reported (Ciegler, Lillehoj, Peterson, & Hall, 1966;Cole & Kirksey, 1971;Harvey, Kubena, Phillips, Huff, & Corrier, 1989;Mann & Rehm, 1976). These include chemical detoxification by ammoniation (Coker, Jewers, & Jones, 1985;Frayssinet & Lafarge, 1990;Gardner, Koltun, Dollear, & Rayner, 1971), treatment with formaldehyde and calcium hydroxide (Codifer, Mann, & Dollear, 1976), ozonization (Dwarakanath, Rayner, Mann, & Dollear, 1968), exposure to chlorine gas (Fischbach & Campbell, 1965) and hydrogen peroxide (Sreenivasamurthy, Parpia, Srikanta, & Shankar Murti, 1967). Other effective methods include microbial detoxification by Flavobacterium aurantiacum (Ciegler et al, 1966;Hao & Brackett, 1988), Mucor sp.…”
Section: Introductionmentioning
confidence: 95%
“…acetic acid (Pons et al, 1981) ammonia gas or NH 4 OH (Brekke et al, 1977;Moerch et al, 1980) ammonium salts, 3-5% (Brekke et al, 1977) calcium hydroxide (Codifier et al, 1976) formaldehyde (Codifier et al, 1976;Mann et al, 1970) hydrogen peroxide (Spreenivasamurthy et al, 1967) methylamine (Park et al, 1983) ozone gas (Dwaratanath et al, 1968) phosphoric acid (Mann et al, 1970) phosphine gas -sodium bicarbonate (Mashaly et al, 1983) sodium bisulfite (Moerch et al, 1980) sodium bisulfite (Moerch et al, 1980;Mashaly et al, 1983) sodium hypochlorite (Yang, 1972) …”
Section: Pharmacokinetics……………………………………… 341mentioning
confidence: 99%
“…It has been used in water treatment for disinfection and oxidative decomposition. Though Dwarakanath et al (1968) reported that ozone reduced aflatoxin in cottonseed meal and peanut meal, there are no reports on the reactivity of ozone with aflatoxins.…”
Section: Rat Toxicity Testmentioning
confidence: 99%